Clustering of Argentinean Tospoviruses with existing species in the genus by sequence analysis of a 450-nucleotide RNA region of the N gene - Dewey, Ricardo Alfredo (1996)
The genomic diversity of Argentine Tospoviruses from different geographical areas, and from several distinct crops was analysed here. For each isolate, RT-PCR, cloning and sequencing of a 450 nt fragment of the N gene were performed. Comparisons of RNA and predicted amino acid sequence identity and similarity were made. A partial sequence of the N gene was able to classify our local isolates within three Tospovirus species previously described (Tomato spotted wilt virus, TSWV; tomato chlorotic spot virus, TCSV and groundnut ringspot virus, GRSV). With the sequence data currently available, we performed a cladistic phylogenetic analysis which gave a possible genealogy among members of the Tospovirus genus.